2005
DOI: 10.1016/j.ejheart.2004.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Combined systolic and diastolic dysfunction in the presence of preserved left ventricular ejection fraction

Abstract: Background: Heart failure with preserved left ventricular ejection fraction (LVEF) suggests isolated diastolic dysfunction. Aim: The purpose of this study was to determine if systolic and diastolic dysfunction occurred with preserved LVEF. Methods: Equilibrium resting radionuclide ventriculograms from 439 patients with an LVEF z0.50 were used to determine LV peak filling rate (PFR) and peak ejection rate ( Conclusions:The results indicate that a preserved LVEF was often associated with LV systolic dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In addition, PER and PFR may vary widely from patient to patient due to patient selection or technical reasons [24]. Despite these limitations, the PER and PFR abnormal values assessed by other authors [25] and those observed in this study are significantly correlated. Our findings thus have a reasonable and consistent clinical validity.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, PER and PFR may vary widely from patient to patient due to patient selection or technical reasons [24]. Despite these limitations, the PER and PFR abnormal values assessed by other authors [25] and those observed in this study are significantly correlated. Our findings thus have a reasonable and consistent clinical validity.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, Bonow and colleagues demonstrated that in healthy patients, neither PFR nor the time to PFR correlated with echocardiographic LV end‐diastolic transverse dimension. Our results do not rule out the possibility that an increase in EDV is associated with a decrease in EF below normal limits because we included only patients with a normal EF in our study. Our results are in agreement with a recent study by cardiac magnetic resonance and by magnetic resonance spectroscopy of patients with stable diabetes mellitus, which reported an altered diastolic function and a decreased LVEF together with altered phosphocreatine metabolism in these patients compared with healthy controls …”
Section: Discussionmentioning
confidence: 81%
“…Recently, the sequential connection of diastolic left ventricular dysfunction, atrial remodeling (atrial cardiopathy), AF, and left atrial thrombus has been emphasized. [31][32][33] Because a substantial portion of patients with diastolic left ventricular dysfunction have LVWMA with a normal ejection fraction, 34 LVWMA may be an early sign of heart failure from diverse etiologies. Echocardiographic parameters associated with LVWMA, including mildly decreased ejection fraction or decreased fractional shortening, have been demonstrated to have harmful effects on stroke.…”
Section: Discussionmentioning
confidence: 99%